Pengaruh Karakteristik Individu, Komitmen Organisasi, dan K3 terhadap Kinerja Karyawan UD Monggo Jaya Kab. Kediri - Dela Citra Tarida; Diana Ambarwati; Nuril Aulia Munawaroh (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of individual characteristics, organizational commitment, and occupational health and safety on employee performance at UD Monggo Jaya, Kediri Regency. A quantitative method is used in this research, with data collection through questionnaires and interviews. The research employs a non-probability sampling technique, utilizing a saturated sample method with a population of 52 employees and a sample size of 52 employees. Based on the results of the study, it shows that partially the individual characteristics variable has a significant effect on employee performance variables, with a Sig. value of 0.033 < 0.05. Partially the organizational commitment variable does not have a significant effect on employee performance variables, with a Sig. value of 0.884> 0.05. Partially the occupational safety and health variable does not have a significant effect on employee performance variables, with a Sig. value of 0.068> 0.05. The individual characteristics, organizational commitment, occupational safety and health variables simultaneously have a significant effect on employee performance at UD Monggo Jaya, Kediri Regency with a Sig. value of 0.028 < 0.05. The influence of the level of individual characteristics, organizational commitment, occupational safety and health on employee performance is 17.1%, while the remaining 82.9% is influenced by other variables not examined in this study.